Trajectory of the arterial-alveolar oxygen gradient in COPD for a decade - Kazuma Nagata; Susumu Sato; Kiyoshi Uemasu; Naoya Tanabe; Atsuyasu Sato; Shigeo Muro; Toyohiro Hirai (PLoS ONE, 2025)
Background Chronic respiratory failure (CRF) is a critical complication in patients with chronic obstructive pulmonary disease (COPD) and is characterized by an increase in the arterial-alveolar oxygen gradient (A-aDO2). The long-term trajectory and prognostic significance remain unclear. This study aimed to assess the prognostic impact of A-aDO2 and elucidate its trajectory over ten years. Methods We enrolled 170 outpatients with COPD from a prospective cohort study. Arterial blood gas (ABG) analyses were conducted annually for ten years while monitoring the development of CRF. Results 157 patients completed the observation period, of whom 21 developed CRF (CRF group) and 136 did not (non-CRF group). In the CRF group, there was a gradual increase in A-aDO2 along with decreases in partial pressure of oxygen (PaO2) and partial pressure of carbon dioxide (PaCO2) over ten years, although there were no changes in the non-CRF group. The CRF group had higher baseline A-aDO2 and higher ΔA-aDO2 in the first year than the non-CRF group (3.76 vs. 0.42 Torr/year, p = 0.030). Kaplan-Meier analyses, and multivariate Cox proportional hazards analysis revealed that both baseline A-aDO2 and ΔA-aDO2 were significantly associated with the development of CRF. Retrospective tracking from the initiation of long-term oxygen therapy (LTOT) revealed significant increases in A-aDO2 from 5 years prior to LTOT initiation in the CRF group when compared to the non-CRF group. Conclusions An increasing trend in A-aDO2 may be a significant sign for the future development of CRF. A transition of the annual change of A-aDO2 from a stable state to a deterioration phase can serve as a prognostic factor for developing CRF within 5 years.